A Conceptual Analysis on Co-operative Enterprise (KOSISWA) at Institute of Higher Learning (IHLs) in Malaysia: Transformation of Malays economies agenda - Fakhrul Anwar, Zainol; Zainudin, Awang; Hardayanna, Abd Rahman; Norazlina, Abdullah; Zaharah, Dzulkifli (2015)
The government initiatives towards establishment of business and entrepreneurs, especially among Malays ethnic, experienced a rapid development since Malaysia Independence Day back in 1957. Various policies have been launched such as New Economic Policy (1970-1990) which aimed to increase Malays ownership in economic activities without ignoring other races. However, at the end of the period, the targeted figure of 30% Malays ownership is far from achieved. The government then invested tones of money to develop various programs to overcome the problems which includes enhancement on cooperative enterprise among Malays. In Malaysia, 6.78 million people or 27% of the total population are members of co-operatives. These co-operative enterprises continue to play significant economic and social roles in the communities. Co-operative provides over 100 million jobs around the world, 20% more than multinational corporations. However, the co-operative enterprises have its own challenges which surrounded on the capacity of its members. Affective commitment may play a significant role specifically associated with determining entrepreneurial orientation among graduates at IHLs via cooperatives enterprise. In doing so, a conceptual model was put forward drawn from the literature to suggest possible antecedent conditions and its consequence associated with affective commitment at cooperative enterprises level. Thus, this study argued that in order to transform the Malays economies in Malaysia it must be done via co-operatives enterprise model since majority of the Malays joined the cooperatives and it already become the third largest sector in the country after government and private sectors. To make co-operative become successful the members of the co-operatives must overcome all the challenges and obstacles. These responsibilities should be upheld by young generation; the graduates at IHLs that will becomes the backbone of co-operative management in the future.